The relation between the types of multiple intelligences and the training departments of candidate teachers - Gürbüzoğlu Yalmancı, Sibel (Journal of Human Sciences, 2011)
The purpose of this study is the comparison of different types of multiple intelligences according to students studying in different departments of Education Faculty. The sample of this study was composed of 191 candidate teachers still studying in Kafkas University Education Faculty in Undergraduate Programs; Class Teacher Education, Social Science Education, Science Education and Turkish Education Programs. In this study one of the survey methods; general survey method was used.“Multiple Intelligences Areas Inventory for Adults” prepared by Ziya Selçuk was applied to students as data collection instrument. For the analysis of data gathered; one-way Anova techniques were used. In the results of the study, it was found that there is a significant difference between the mathematical-logical intelligence, spatial intelligence and interpersonal intelligence and the departments of candidate teachers.